Pelatihan Perhitungan SPT wajib pajak pribadi pada tenaga pendidik di SMK Muhammadiyah 4 Lamongan - Yulis Saidah; Mokhtar Sayyid; Ihsanudin Ihsanudin; Novita Sari (Universitas Muhammadiyah Manado, 2020)
Self-assessment system is a tax collection system that gives confidence to taxpayers to calculate/calculate, pay, and report the amount of tax that should be owed based on tax laws and regulations. Notification Letter (SPT) is a means used by taxpayers to account for the calculation of taxes owed. Understanding for filling out Annual Tax Returns for both individual and corporate taxpayers is needed, including the use of online systems used to deposit and report taxes. LPPM also plays a role in providing tax training through Community Service activities. The purpose of this community service activity is to be able to provide an understanding of how to fill out Annual Tax Returns for individuals and entities as well as the use of e-billing and e-filing for to make deposits and tax reporting. The result achieved in this training is that participants can understand the process of calculating and filling out the Annual Tax Return of individuals and entities as well as how to use e-billing and e-filing. The output target to be achieved from this training is to be able to provide an understanding of taxation to Educators of SMK Muhammadiyah 4 Lamongan in terms of filling out Annual Income Tax Returns for Individuals and Entities, including procedures for depositing and reporting taxes online.